Conductive coating and preparation method thereof

By using modified polyaniline and conductive barium sulfate in conductive coatings and composited with modified acrylic resin, the existing conductive coatings have been solved, and efficient conductive properties and electromagnetic shielding effects are achieved, which are suitable for many industrial fields.

CN119039845BActive Publication Date: 2025-02-28FOSHAN TUYI DECORATIVE MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411549816.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-28
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

In the face of high cost and difficult processing, existing conductive coatings are difficult to meet the conductive performance and electromagnetic shielding requirements of high-frequency, high power, high density and highly integrated electronic devices.

Method used

Modified polyaniline and conductive barium sulfate are used as filler components, combined with modified acrylic resin as the base material, and added curing agent, wetting agent, dispersing agent, defoaming agent and thickening agent to prepare conductive coatings through a composite process.

Benefits of technology

It has achieved good electrical conductivity and electromagnetic shielding effect of conductive coatings, has a wide range of application prospects, and does not contain harmful solvents and organic volatiles, which is harmless to the environment and human health.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the field of functional coatings, and the present invention discloses a conductive coating and a preparation method thereof. The conductive coating provided by the present invention comprises: a filler component A, a base material component B, an auxiliary agent C and deionized water, and in parts by weight: the filler component A comprises: 30-60 parts of modified polyaniline, 20-40 parts of conductive barium sulfate; the base material component B comprises: 400-600 parts of modified acrylic resin; the auxiliary agent C comprises: 20-40 parts of curing agent, 5-10 parts of wetting agent, 1-5 parts of dispersant, 1-5 parts of defoaming agent, and 1-5 parts of thickener. The conductive coating prepared by the present invention using modified polyaniline and other components as conductive fillers and modified acrylic resin as base material has good conductive properties and electromagnetic shielding effect, and has a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional coatings, and in particular relates to a conductive coating and a preparation method thereof. Background Art

[0002] With the rapid development of computer and semiconductor technology, emerging electronic information technology is widely used in unmanned systems, high-speed communications, industrial Internet, aerospace and other fields. The rapid development of the information technology industry has placed higher requirements on electronic equipment and components. Achieving high frequency, high power, high density and high integration is the current main development direction. In this process, there will be problems of electromagnetic interference and static electricity. Conductive coating is a functional coating that can form a conductive cured film on the surface of the substrate by spraying or brushing. It can give the material conductive properties and electromagnetic shielding properties. It has been used in many industrial fields such as aviation, electronics, construction, chemicals and printing. In recent years, two-dimensional crystalline materials with excellent performance have begun to be applied to conductive coatings, but they are costly and difficult to process. Therefore, it is necessary to develop a conductive coating with good conductivity and a wide range of usage scenarios. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a conductive coating and a preparation method thereof.

[0004] The present invention provides a conductive coating, comprising: a filler component A, a base material component B, an additive C and deionized water, in parts by weight:

[0005] The filler component A comprises: 30-60 parts of modified polyaniline and 20-40 parts of conductive barium sulfate;

[0006] The base material component B comprises: 400-600 parts of modified acrylic resin;

[0007] The auxiliary agent C comprises: 20-40 parts of a curing agent, 5-10 parts of a wetting agent, 1-5 parts of a dispersant, 1-5 parts of a defoaming agent, and 1-5 parts of a thickener.

[0008] Preferably, the conductive coating includes deionized water, and further includes, by weight: 40-60 parts of modified polyaniline, 20-35 parts of conductive barium sulfate, 450-550 parts of modified acrylic resin, 20-30 parts of curing agent, 5-10 parts of wetting agent, 1-5 parts of dispersant, 1-5 parts of defoaming agent, and 1-5 parts of thickener.

[0009] Preferably, the conductive coating includes deionized water, and further includes, by weight: 40-50 parts of modified polyaniline, 25-35 parts of conductive barium sulfate, 450-500 parts of modified acrylic resin, 25-30 parts of curing agent, 5-10 parts of wetting agent, 1-5 parts of dispersant, 1-5 parts of defoaming agent, and 1-5 parts of thickener.

[0010] Preferably, the modified acrylic resin is obtained by modifying the acrylic resin with trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and the usage ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1wt%:(20-25)wt%.

[0011] Preferably, the modified polyaniline is obtained by doping polyaniline with camphorsulfonic acid, comprising the following steps:

[0012] Step S11: dissolving camphorsulfonic acid in N-methylpyrrolidone, and obtaining a camphorsulfonic acid solution by ultrasonication;

[0013] Step S12: placing polyaniline in ammonia water, stirring for 48 hours, filtering and washing to obtain a solid;

[0014] Step S13: adding the solid to N-methylpyrrolidone, keeping stirring, and gradually adding camphorsulfonic acid solution, filtering and washing to obtain the solid, and drying to obtain the modified polyaniline.

[0015] Preferably, the filler component A further comprises 5-10 parts of modified nano-metal particles, wherein the modified nano-metal particles comprise nano-copper powder and nano-zinc powder, which are obtained by mixing and modifying the nano-copper powder and the nano-zinc powder at a mass ratio of 1:(5-8). The modification steps of the modified nano-metal particles include:

[0016] Step S21: Mix the nano copper powder and the nano zinc powder according to a certain proportion and stir them evenly;

[0017] Step S22: adding vinyl triethoxysilane to the mixed metal particles and stirring;

[0018] Step S23: adding the mixture of step S22 into anhydrous ethanol and performing ultrasonic dispersion;

[0019] Step S24: After the ultrasonic dispersion is completed, the particles are filtered and dried to obtain modified nano-metal particles.

[0020] Preferably, the curing agent is triglycidyl isocyanurate.

[0021] Preferably, the wetting agent is alkyl polyoxyethylene ether and / or polyoxyethylene alkylphenol ether.

[0022] Preferably, the defoaming agent is a mineral oil defoaming agent or a polysiloxane defoaming agent.

[0023] The present invention also provides a method for preparing the conductive coating as described in any one of the above, comprising the following steps:

[0024] Step S31: weigh filler component A and deionized water according to a ratio of 1:(10-20), add deionized water into a disperser, and stir at a speed of 500-800 r / min;

[0025] Step S32: gradually adding filler component A into the disperser in multiple times, stirring for 0.5-1h to obtain a dispersion of filler component A;

[0026] Step S33: ultrasonically dispersing the filler component A dispersion for 0.5-1h, adding a dispersant thereto and stirring for 10-20min at a speed of 300-500r / min, then adding a defoaming agent and continuing stirring for 10-20min to obtain a conductive slurry;

[0027] Step S34: Add the above conductive paste to the base material component B, and add a wetting agent, a curing agent, and a defoaming agent in sequence, stir for 15-30 minutes, then add a thickener, and stir for 5-10 minutes to obtain a conductive coating.

[0028] The conductive coating provided by the present invention has at least the following beneficial effects:

[0029] 1. This scheme uses modified polyaniline and other components as conductive fillers and modified acrylic resin as the base material to prepare a conductive coating with good conductive properties. The formed coating can prevent static electricity accumulation and has a good electromagnetic shielding effect. It can be widely used in electronic components, electromagnetic shielding, anti-static and other fields, and has broad application prospects.

[0030] 2. The conductive coating of this scheme has good anti-corrosion and mechanical properties.

[0031] 3. The conductive coating of this solution does not contain harmful solvents and volatile organic compounds, is harmless to the environment and human health, and reduces the risk of indoor air pollution. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0033] The conductive coating provided by the present invention is a composite conductive coating, that is, a filled conductive coating. The coating has conductive properties and electromagnetic shielding effectiveness by adding composite conductive fillers.

[0034] The embodiment of the present invention provides a conductive coating, including: a filler component A, a base material component B, an additive C and deionized water, in parts by weight:

[0035] Filler component A includes: 30-60 parts of modified polyaniline and 20-40 parts of conductive barium sulfate;

[0036] Base material component B includes: 400-600 parts of modified acrylic resin;

[0037] The additive C comprises: 20-40 parts of curing agent, 5-10 parts of wetting agent, 1-5 parts of dispersant, 1-5 parts of defoaming agent and 1-5 parts of thickener.

[0038] Preferably, the conductive coating includes deionized water, and further includes, by weight: 40-60 parts of modified polyaniline, 20-35 parts of conductive barium sulfate, 450-550 parts of modified acrylic resin, 20-30 parts of curing agent, 5-10 parts of wetting agent, 1-5 parts of dispersant, 1-5 parts of defoaming agent, and 1-5 parts of thickener.

[0039] Preferably, the conductive coating includes deionized water, and further includes, by weight: 40-50 parts of modified polyaniline, 25-35 parts of conductive barium sulfate, 450-500 parts of modified acrylic resin, 25-30 parts of curing agent, 5-10 parts of wetting agent, 1-5 parts of dispersant, 1-5 parts of defoaming agent, and 1-5 parts of thickener.

[0040] Preferably, the modified acrylic resin is obtained by modifying the acrylic resin with trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and the usage ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1wt%:(20-25)wt%.

[0041] Preferably, the modified polyaniline is obtained by doping polyaniline with camphorsulfonic acid, comprising the following steps:

[0042] Step S11: dissolving camphorsulfonic acid in N-methylpyrrolidone, and obtaining a camphorsulfonic acid solution by ultrasonication;

[0043] Step S12: placing polyaniline in ammonia water, stirring for 48 hours, filtering and washing to obtain a solid;

[0044] Step S13: adding the solid to N-methylpyrrolidone, keeping stirring, and gradually adding camphorsulfonic acid solution, filtering and washing to obtain the solid, and drying to obtain the modified polyaniline.

[0045] Preferably, the filler component A further comprises 5-10 parts of modified nano-metal particles, wherein the modified nano-metal particles comprise nano-copper powder and nano-zinc powder, which are obtained by mixing and modifying the nano-copper powder and the nano-zinc powder at a mass ratio of 1:(5-8). The modification steps of the modified nano-metal particles include:

[0046] Step S21: Mix the nano copper powder and the nano zinc powder according to a certain proportion and stir them evenly;

[0047] Step S22: adding vinyl triethoxysilane to the mixed metal particles and stirring;

[0048] Step S23: adding the mixture of step S22 into anhydrous ethanol and performing ultrasonic dispersion;

[0049] Step S24: After the ultrasonic dispersion is completed, the particles are filtered and dried to obtain modified nano-metal particles.

[0050] Preferably, the curing agent is triglycidyl isocyanurate.

[0051] Preferably, the wetting agent is alkyl polyoxyethylene ether and / or polyoxyethylene alkylphenol ether.

[0052] Preferably, the defoaming agent is a mineral oil defoaming agent or a polysiloxane defoaming agent.

[0053] The present invention also provides a method for preparing the conductive coating as described above, comprising the following steps:

[0054] Step S31: weigh filler component A and deionized water according to a ratio of 1:(10-20), add deionized water into a disperser, and stir at a speed of 500-800 r / min;

[0055] Step S32: gradually adding filler component A into the disperser in multiple times, stirring for 0.5-1h to obtain a dispersion of filler component A;

[0056] Step S33: ultrasonically dispersing the filler component A dispersion for 0.5-1h, adding a dispersant thereto and stirring for 10-20min at a speed of 300-500r / min, then adding a defoaming agent and continuing stirring for 10-20min to obtain a conductive slurry;

[0057] Step S34: Add the above conductive paste to the base material component B, and add a wetting agent, a curing agent, and a defoaming agent in sequence, stir for 15-30 minutes, then add a thickener, and stir for 5-10 minutes to obtain a conductive coating.

[0058] To better illustrate the solutions of the present invention, the following are specific embodiments.

[0059] Example 1

[0060] The raw materials of the conductive coating are: 500 parts of deionized water, 30 parts of modified polyaniline, 20 parts of conductive barium sulfate, 400 parts of modified acrylic resin, 20 parts of curing agent, 5 parts of wetting agent, 2 parts of dispersant, 2 parts of defoaming agent, and 1 part of thickener. Among them, when modifying acrylic resin, the amount ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:20.

[0061] Preparation method:

[0062] Weigh modified polyaniline, conductive barium sulfate and deionized water according to the proportion, add the deionized water into the disperser, and stir at a speed of 500 r / min;

[0063] The modified polyaniline and the conductive barium sulfate were gradually added into the disperser in multiple times, and stirred for 0.5 hours to obtain a filler component dispersion;

[0064] The filler component dispersion was ultrasonicated for 0.5 h, a dispersant was added thereto and stirred for 10 min at a speed of 300 r / min, a defoamer was added thereto, and stirring was continued for 10 min to obtain a conductive slurry;

[0065] The conductive paste was added to the modified acrylic resin, and a wetting agent, a curing agent, and a defoaming agent were added in sequence, and stirred for 15 minutes. Then, a thickener was added and stirred for 5 minutes to obtain a conductive coating.

[0066] Example 2

[0067] The raw materials of the conductive coating are: 750 parts of deionized water, 45 parts of modified polyaniline, 30 parts of conductive barium sulfate, 500 parts of modified acrylic resin, 30 parts of curing agent, 7 parts of wetting agent, 3 parts of dispersant, 3 parts of defoaming agent, and 2 parts of thickener. Among them, when modifying the acrylic resin, the amount ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:20.

[0068] Preparation method:

[0069] Weigh modified polyaniline, conductive barium sulfate and deionized water according to the proportion, add the deionized water into the disperser, and stir at a speed of 500 r / min;

[0070] The modified polyaniline and the conductive barium sulfate were gradually added into the disperser in multiple times, and stirred for 0.5 hours to obtain a filler component dispersion;

[0071] The filler component dispersion was ultrasonicated for 0.5 h, a dispersant was added thereto and stirred for 10 min at a speed of 300 r / min, a defoamer was added thereto, and stirring was continued for 10 min to obtain a conductive slurry;

[0072] The conductive paste was added to the modified acrylic resin, and a wetting agent, a curing agent, and a defoaming agent were added in sequence, and stirred for 15 minutes. Then, a thickener was added and stirred for 5 minutes to obtain a conductive coating.

[0073] Example 3

[0074] The raw materials of the conductive coating are: 1000 parts of deionized water, 60 parts of modified polyaniline, 40 parts of conductive barium sulfate, 600 parts of modified acrylic resin, 40 parts of curing agent, 10 parts of wetting agent, 4 parts of dispersant, 4 parts of defoaming agent, and 3 parts of thickener. Among them, when modifying acrylic resin, the usage ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:20.

[0075] Preparation method:

[0076] Weigh modified polyaniline, conductive barium sulfate and deionized water according to the proportion, add the deionized water into the disperser, and stir at a speed of 500 r / min;

[0077] The modified polyaniline and the conductive barium sulfate were gradually added into the disperser in multiple times, and stirred for 0.5 hours to obtain a filler component dispersion;

[0078] The filler component dispersion was ultrasonicated for 0.5 h, a dispersant was added thereto and stirred for 10 min at a speed of 300 r / min, a defoamer was added thereto, and stirring was continued for 10 min to obtain a conductive slurry;

[0079] The conductive paste was added to the modified acrylic resin, and a wetting agent, a curing agent, and a defoaming agent were added in sequence, and stirred for 15 minutes. Then, a thickener was added and stirred for 5 minutes to obtain a conductive coating.

[0080] Example 4

[0081] The raw materials of the conductive coating are: 500 parts of deionized water, 30 parts of modified polyaniline, 20 parts of conductive barium sulfate, 5 parts of modified nano-metal particles, 400 parts of modified acrylic resin, 20 parts of curing agent, 5 parts of wetting agent, 2 parts of dispersant, 2 parts of defoaming agent, and 1 part of thickener. Among them, when modifying acrylic resin, the amount ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:20.

[0082] Preparation method:

[0083] Weigh modified polyaniline, conductive barium sulfate, modified nano-metal particles and deionized water according to the proportion, add the deionized water into the disperser, and stir at a speed of 500 r / min;

[0084] The modified polyaniline and the conductive barium sulfate were gradually added into the disperser in multiple times, and stirred for 0.5 hours to obtain a filler component dispersion;

[0085] The filler component dispersion was ultrasonicated for 0.5 h, a dispersant was added thereto and stirred for 10 min at a speed of 300 r / min, a defoamer was added thereto, and stirring was continued for 10 min to obtain a conductive slurry;

[0086] The conductive paste was added to the modified acrylic resin, and a wetting agent, a curing agent, and a defoaming agent were added in sequence, and stirred for 15 minutes. Then, a thickener was added and stirred for 5 minutes to obtain a conductive coating.

[0087] Example 5

[0088] The raw materials of the conductive coating are: 500 parts of deionized water, 30 parts of modified polyaniline, 20 parts of conductive barium sulfate, 400 parts of modified acrylic resin, 20 parts of curing agent, 5 parts of wetting agent, 2 parts of dispersant, 2 parts of defoaming agent, and 1 part of thickener. Among them, when modifying acrylic resin, the amount ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:25.

[0089] Preparation method:

[0090] Weigh modified polyaniline, conductive barium sulfate and deionized water according to the proportion, add the deionized water into the disperser, and stir at a speed of 500 r / min;

[0091] The modified polyaniline and the conductive barium sulfate were gradually added into the disperser in multiple times, and stirred for 0.5 hours to obtain a filler component dispersion;

[0092] The filler component dispersion was ultrasonicated for 0.5 h, a dispersant was added thereto and stirred for 10 min at a speed of 300 r / min, a defoamer was added thereto, and stirring was continued for 10 min to obtain a conductive slurry;

[0093] The conductive paste was added to the modified acrylic resin, and a wetting agent, a curing agent, and a defoaming agent were added in sequence, and stirred for 15 minutes. Then, a thickener was added and stirred for 5 minutes to obtain a conductive coating.

[0094] Comparative Example 1

[0095] The difference from Example 1 is that no modified polyaniline is added.

[0096] Comparative Example 2

[0097] The difference from Example 1 is that the modified polyaniline is replaced by polyaniline.

[0098] Comparative Example 3

[0099] The difference from Example 1 is that the modified acrylic resin is replaced by acrylic resin.

[0100] Comparative Example 4

[0101] Different from Example 1, when modifying the acrylic resin, the usage ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:10.

[0102] Comparative Example 5

[0103] Different from Example 1, when modifying the acrylic resin, the usage ratio of trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1:40.

[0104] Comparative Example 6

[0105] The difference from Example 1 is that no barium sulfate is added.

[0106] The coatings prepared in Examples 1-5 and Comparative Examples 1-6 were subjected to surface coating tests, including a conductivity test (conductivity was tested using a four-probe method), an electromagnetic shielding effectiveness test (tested within the X-band (8.2-12.4 GHz) frequency range), a coating hardness test (GB / T 6739-2022), a coating adhesion test (GB / T 9286-2022), a coating impact resistance test (GB / T 20624.2-2006, Part 2, drop hammer test), an acid salt spray (AASS) test (GB / T 10125-2012), and an alkali resistance test (immersion in a 10% NaOH solution). The following are the specific test results.

[0107] As can be seen from Table 1 below, it can be seen from Examples 1 to 3 that the conductive coating of this scheme has good conductivity and electromagnetic shielding effectiveness, and has good mechanical properties and corrosion resistance; it can be seen from Example 4 that after further adding modified nano-metal particles, the conductive properties of the coating can be improved, but the electromagnetic shielding effectiveness has little effect; it can be seen from Example 5 that increasing the amount of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane when modifying the acrylic resin can further improve the mechanical properties of the coating.

[0108] Table 1 Test results

[0109]

[0110] Further, it can be seen from Example 1 and Comparative Examples 1 and 2 that, without adding modified polyaniline, the conductive properties and electromagnetic shielding effect of the coating are significantly reduced; and when the modified polyaniline is replaced with ordinary polyaniline, the conductive properties and electromagnetic shielding effect of the coating are also significantly reduced; from Example 1 and Comparative Examples 3-5, it can be seen that when the modified acrylic resin is replaced with ordinary acrylic resin, the mechanical properties of the coating are reduced; and when different modified acrylic resins are used, if the amount of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is too high or too low, the mechanical properties of the coating will be significantly reduced, and the reduction is greater than that of ordinary acrylic resin; from Example 1 and Comparative Example 6, it can be seen that when barium sulfate is not added, the conductive properties and electromagnetic shielding effectiveness of the coating are also reduced to a certain extent.

[0111] Furthermore, it can be seen that the conductive coating provided by the present invention is obtained by compounding and adding conductive coatings such as modified polyaniline to modified acrylic resin. The modified polyaniline has better conductivity and electromagnetic shielding effectiveness, while the modified acrylic resin enables the coating to have better mechanical properties and corrosion resistance. By compounding other conductive fillers, the performance of the coating is further improved.

[0112] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A conductive coating, characterized in that: In parts by weight, it includes: 60 parts of modified polyaniline, 40 parts of conductive barium sulfate, 600 parts of modified acrylic resin, 40 parts of curing agent, 10 parts of wetting agent, 4 parts of dispersant, 4 parts of defoaming agent, 3 parts of thickener, 1000 parts of deionized water; and also includes 5-10 parts of modified nano metal particles; The modified acrylic resin is obtained by modifying acrylic resin with trimethylolpropane triacrylate and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, wherein the amount ratio of trimethylolpropane triacrylate to N-(2-aminoethyl)-3-aminopropyltrimethoxysilane is 1wt%:20wt%; The modified polyaniline is obtained by doping polyaniline with camphorsulfonic acid, comprising the following steps: Step S11: dissolving camphorsulfonic acid in N-methylpyrrolidone, and obtaining a camphorsulfonic acid solution by ultrasonication; Step S12: placing polyaniline in ammonia water, stirring for 48 hours, filtering and washing to obtain a solid; Step S13: adding the solid to N-methylpyrrolidone, keeping stirring, and gradually adding camphorsulfonic acid solution, filtering and washing to obtain the solid, and drying to obtain the modified polyaniline; The modified nano-metal particles include nano-copper powder and nano-zinc powder, which are obtained by mixing and modifying the nano-copper powder and the nano-zinc powder at a mass ratio of 1:(5-8). The modification steps of the modified nano-metal particles include: Step S21: Mix the nano copper powder and the nano zinc powder according to a certain proportion and stir them evenly; Step S22: adding vinyl triethoxysilane to the mixed metal particles and stirring; Step S23: adding the mixture of step S22 into anhydrous ethanol and performing ultrasonic dispersion; Step S24: filtering and drying after ultrasonic dispersion to obtain modified nano-metal particles; The curing agent is triglycidyl isocyanurate; The wetting agent is alkyl polyoxyethylene ether and / or polyoxyethylene alkylphenol ether; The defoamer is a mineral oil defoamer or a polysiloxane defoamer.

2. A method for preparing a conductive coating as claimed in claim 1, characterized in that: The following steps are involved: Step S31: Weigh modified polyaniline, conductive barium sulfate and deionized water according to proportion, add deionized water into a disperser, and stir at a speed of 500-800 r / min; Step S32: gradually adding modified polyaniline and conductive barium sulfate into a disperser in multiple times, stirring for 0.5-1h, to obtain a dispersion of filler component A; Step S33: ultrasonically dispersing the filler component A dispersion for 0.5-1h, adding a dispersant thereto and stirring for 10-20min at a speed of 300-500r / min, then adding a defoaming agent and continuing stirring for 10-20min to obtain a conductive slurry; Step S34: Add the above conductive paste to the modified acrylic resin, and add a wetting agent, a curing agent, and a defoaming agent in sequence, stir for 15-30 minutes, then add a thickener, stir for 5-10 minutes, and obtain a conductive coating.

Citation Information

Patent Citations

  • Electromagnetic shielding conductive coating and preparation method thereof

    CN102618145A

  • Conductive self-cleaning hydrophilic coating

    CN105017889A

  • Modified anticorrosive anti-shielding antistatic shellac varnish

    CN105086817A

  • Conductive coating and preparation method thereof

    CN112940604A

  • Anti-static EVA and preparation method thereof

    CN114133653A